2022
DOI: 10.1007/s40195-021-01351-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Mechanical Properties of AA5083 Matrix Composite via Introducing Al0.5CoCrFeNi Particles and Cryorolling

Abstract: High-entropy alloy particles (HEAPs) can markedly enhance the mechanical properties of metal matrix composites (MMCs). In this study, AA5083/Al 0.5 CoCrFeNi HEAPs MMCs with different HEAPs contents (0, 1, and 3 wt%) were prepared via a stir-casting, and then these MMCs sheets were hot rolled (573 K) and cryorolled (77 K), respectively. The mechanical properties of the MMCs sheets were measured by tensile testing and microhardness test. Additionally, their microstructures were analyzed by scanning electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…[ 40 ] Navya et al [ 41 ] analyzed the effects of CR on pure aluminum and found that the cryogenic temperature inhibits dynamic recovery, leading to improvements in yield and tensile strength, as well as material hardness. According to previous studies, [ 42–44 ] ARB with CR might significantly enhance the mechanical characteristics of an aluminum matrix. However, there are few studies on the ARB with CR of AMCs with nanoparticle reinforcement in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 ] Navya et al [ 41 ] analyzed the effects of CR on pure aluminum and found that the cryogenic temperature inhibits dynamic recovery, leading to improvements in yield and tensile strength, as well as material hardness. According to previous studies, [ 42–44 ] ARB with CR might significantly enhance the mechanical characteristics of an aluminum matrix. However, there are few studies on the ARB with CR of AMCs with nanoparticle reinforcement in the literature.…”
Section: Introductionmentioning
confidence: 99%